Secondary analysis of teaching methods in introductory physics: A 50 k-student study - Von Korff, J.; Archibeque, Benjamin; Gomez, K. Alison; Heckendorf, T.; McKagan, S. B.; Sayre, Eleanor C.; Schenk, Edward W.; Shepherd, C.; Sorell, L. (My University, 2016)
Physics education researchers have developed many evidence-based instructional strategies to enhance conceptual learning of students in introductory physics courses. These strategies have historically been tested using assessments such as the Force Concept Inventory (FCI) and the Force and Motion Conceptual Evaluation (FMCE). We have performed a review and analysis of FCI and FMCE data published between 1995 and 2014. We confirm previous findings that interactive engagement teaching techniques are significantly more likely to produce high student learning gains than traditional lecture-based instruction. We also establish that interactive engagement instruction works in many settings, including those with students having a high and low level of prior knowledge, at liberal arts and research universities, and enrolled in both small and large classes. (C) 2016 Author(s).
Citation: Von Korff, J., Archibeque, B., Gomez, K. A., Heckendorf, T., McKagan, S. B., Sayre, E. C., . . . Sorell, L. (2016). Secondary analysis of teaching methods in introductory physics: A 50 k-student study. American Journal of Physics, 84(12), 969-974. doi:10.1119/1.4964354
Keywords: Motion Conceptual Evaluation; Instruction; Performance; Force; Education & Educational Research; Physics